The worldwide burden of smoking‐related oral cancer deaths - Riccardo Nocini; Giuseppe Lippi; Camilla Mattiuzzi (Wiley, 2020)
Abstract Objectives Although it is now established that cigarette smoking enhances the risk of oral malignancies, less is known on this epidemiologic interplay. Therefore, this brief report aims to provide an update on the worldwide burden of smoking‐related deaths for lip and oral cavity cancers. Material and methods We performed an electronic search in Global Health Data Exchange registry using the keywords "lip and oral cavity cancer" and "smoking," combined with "deaths," "year," and "location." Results Global mortality for lip and oral cavity cancers has considerably grown during the past three decades, exhibiting a 1.40‐fold increase. Although up to one third (i.e.,30.5%) of worldwide deaths for these malignancies are still attributable to cigarette smoking, smoking‐related mortality for oral malignancies has decreased during the past three decades. The impact of cigarette smoking on these deaths is lower (i.e.,18.7%, gradually decreasing) in Africa, whereby the burden is higher in Europe (i.e.,43.7%) and Western Pacific (40.9%, gradually escalating). Conclusions Despite recent policies of smoking dissuasion may have contributed to mitigating the negative impact of smoking on oral cancers, additional healthcare interventions shall be planned to reduce the still high mortality, especially in Western Pacific.